Role Lean Accounting in Support Corporate Governance to Achieve a Competitive Advantage: An Application Study in Diala State Company for Electrical industrial (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The modern business environment has witnesses tremendous developments as a result of the globalization of markets and economic openness and technological as well as the acquisition of the issue of corporate governance of great importance regarding it as one of the global innovations trends of control provisions on the management of companies as result of these developments ,increasing on competition between economic unit ,thus a decrease in market share because they do not take into account the response to the requirements of customers ,which kept her to search a modern management accounting methods to help them keep up with the changes and the availability of information for the various administrative levels for companies and improve its competitive position. The current study gained its importance through the availability of framework applied in the strengthening of corporate governance through the recent trend of the state in the application of corporate governance of state owned using the methods of modern management and focusing on the application of  graceful accounting ,which is the most available of information for management for both levels a management council and executive management thus to achieve a competitive          advantage through customer satisfaction . The study aimed to pay attention to the application of lean  accounting because of their active role to increase the strengthening of the system of corporate governance and to identify the term governance of its various aspects referring to the importance of the application and the positive impact of the accounting methods of modern management on the strengthening of corporate governance focusing the concept of customer satisfaction as a essential feature to achieve a competitive advantage.